A quantitative review of ecosystem service studies: approaches, shortcomings and the road ahead - Seppelt, Ralf; Dormann, Carsten F.; Lautenbach, Sven (Journal of applied ecology, 2011)
1. Ecosystem services are defined as the benefits that humans obtain from ecosystems. Employing the ecosystem service concept is intended to support the development of policies and instruments that integrate social, economic and ecological perspectives. In recent years, this concept has become the paradigm of ecosystem management. 2. The prolific use of the term ‘ecosystem services’ in scientific studies has given rise to concerns about its arbitrary application. A quantitative review of recent literature shows the diversity of approaches and uncovers a lack of consistent methodology. 3. From this analysis, we have derived four facets that characterise the holistic ideal of ecosystem services research: (i) biophysical realism of ecosystem data and models; (ii) consideration of local trade-offs; (iii) recognition of off-site effects; and (iv) comprehensive but critical involvement of stakeholders within assessment studies. 4. These four facets should be taken as a methodological blueprint for further development and discussion. They should critically reveal and elucidate what may often appear to be ad-hoc approaches to ecosystem service assessments. 5. Synthesis and applications: Based on this quantitative review, we provide guidelines for further development and discussions supporting consistency in applications of the ecosystem service concept as well as the credibility of results, which in turn can make it easier to generalise from the numerous individual studies.